Peran Guru dan Orang Tua dalam Pendidikan Anak - Samosir, Pesta (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
Abstract: The role of teachers and parents as educators in teaching Bible truth is very important which aims to produce the character and spiritual qualities of children leading to maturity in thinking and acting. Teachers and parents are each responsible and play a role in educating children with care and affection. At school, teachers can communicate well with children through creative learning, methods, learning styles and appropriate curriculum for children. Provide advice, motivation and encouragement to children to continue to learn and be disciplined as a result of the PAK learning process that is not rigid and boring. The role of parents at home in educating their children is much greater because they spend more time with their children. The presence of parents at home is also an educator in relation to Christian religious education to instill Christian values in children. Teachers and parents can cooperate and synergize in providing teaching to children in order to know the development of children in accordance with the learning outcomes that have been previously planned. The role of parents and teachers as models and role models is to set a good example.Keywords: roles, teachers, parents, studentsÂ Abstrak:Peran guru dan orang tua sebagai pendidik dalam mengajarkan kebenaran Alkitab adalah sangat penting yang bertujuan menghasilkan karakter dan kualitas kerohanian anak yang sangat baik. Guru dan orang tua masing-masing bertanggung jawab dan berperan dalam mendidik anak dengan perhatian dan kasih saying. Di sekolah, guru dapat berkomunikasi secara baik dengan anak melalui pembelajaran yang kreatif, metode, gaya belajar dan kurikulum yang tepat kepada anak-anak. Memberikan nasihat, motivasi dan dorongan kepada anak untuk terus semangat belajar serta disiplin sebagai hasil dari proses pembelajaran PAK yang tidak kaku dan membosankan. Peran orang tua di rumah dalam mendidik anak jauh lebih besar karena waktu yang lebih banyak bersama dengan anak. Keberadaan orang tua di rumah juga adalah sebagai pendidik dalam hubungannya dengan pendidikan agama kristen untuk menanamkan nilai-nilai kekristenan dalam diri anak. Guru dan orang tua dapat menjalin kerja sama dan bersinergi dalam memberikan pengajaran kepada anak demi untuk mengetahui perkembangan anak sesuai dengan capaian pembelajaran yang sudah direncanakan sebelumnya. Peran orang tua dan guru sebagai model dan teladan adalah memberikan contoh yang baik.Kata Kunci: peran, guru, orang tua, anak didik